Chemoenzymatic Synthesis of Asymmetrical Multi‐Antennary N‐Glycans to Dissect Glycan‐Mediated Interactions between Human Sperm and Oocytes. Issue 31 (9th May 2018) - Chinoy, Zoeisha S.; Friscourt, Frédéric; Capicciotti, Chantelle J.; Chiu, Philip; Boons, Geert‐Jan
Abstract: Complex N ‐glycans of glycoproteins of the zona pellucida (ZP) of human oocytes have been implicated in the binding of spermatozoa. The termini of these unusual bi‐, tri‐, and tetra‐antennary N ‐glycans consist of the tetrasaccharide sialyl‐Lewis x (SLe x ), which was previously identified as the minimal epitope for sperm binding. We describe here the chemoenzymatic synthesis of highly complex triantennary N ‐glycans derived from ZP carrying SLe x moieties at the C‐2 and C‐2′ arm and a sialyl‐Lewis x ‐Lewis x (SLe x –Le x ) residue at the C‐6 antenna and two closely related analogues. The compounds were examined for their ability to inhibit the interaction of human sperm to ZP. It was found that the SLe x –Le x moiety is critical for inhibitory activity, whereas the other SLe x moieties exerted minimal effect. Further studies with SLe x –Le x and SLe x showed that the extended structure is the more potent inhibitor. In addition, trivalent SLe x –Le x and SLe x were prepared which showed greater inhibitory activity compared to their monovalent counterparts. Our studies show that although SLe x can inhibit the binding of spermatozoa, presenting this epitope in the context of a complex N ‐glycan results in a loss of inhibitory potential, and in this context only SLe x –Le x can make productive interactions. It is not the multivalent display of SLe x on a multi‐antennary glycan but the presentation of multiple SLe x –Le x on the various glycosylation sites of ZP that accounts for high avidity binding. Abstract : Sugary fertility : A chemoenzymatic approach made it possible to prepare highly complex tri‐antennary glycans derived from human oocytes. Biological studies have shown that although sialyl Lewis x (SLe x ) can inhibit the binding of spermatozoa to oocytes, presenting this epitope in the context of a complex N ‐glycan results in a loss of inhibitory potential, and in this context only SLe x –Le x epitopes can make productive interactions.